Psilocybin-assisted therapy for depression: How do we advance the field?. (March 2020) - Meikle, Sally E; Liknaitzky, Paul; Rossell, Susan L; Ross, Margaret; Strauss, Nigel; Thomas, Neil; Murray, Greg; Williams, Martin; Castle, David J
In the quest for new treatment options for depression, attention is being paid to the potential role of psychedelic drugs. Psilocybin is of particular interest given its mechanism of action, its benefits in early trials and its relatively low side effects burden. This viewpoint outlines a number of key issues that remain to be elucidated about its potential use in the clinical environment, including clarification of the profile of people most likely to benefit and those who might experience adverse effects, longer-term outcomes and the role of psychotherapeutic input alongside the drug itself. There are also opportunities to understand better, the neurobiology underpinning its effects.